(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Shurtan Gas Chemical Complex is one of the largest gas companies in Uzbekistan. Uzbekneftegaz is a unitary subsidiary of the national holding company. It is located in Shurtan town of Guzar district of Kashkadarya region. It occupies an area of more than 150 hectares.